Cross-Sex Hormones and Metabolic Parameters in Adolescents With Gender Dysphoria - Jarin, Jason; Pine-Twaddell, Elyse; Trotman, Gylynthia; Stevens, Jaime; Conard, Lee Ann; Tefera, Eshetu; Gomez-Lobo, Veronica (Pediatrics (Evanston), 2017)
The Endocrine Society states that adolescents with gender dysphoria may start cross-sex hormones. The goal of this study was to identify patterns in metabolic parameters in transgender adolescents receiving cross-sex hormones. Data from adolescents aged 14 to 25 years seen in 1 of 4 clinical sites between 2008 and 2014 were retrospectively analyzed. Subjects were divided into affirmed male (female-to-male) patients taking testosterone and affirmed female (male-to-female) patients taking estrogen. Previously recorded measurements of blood pressure, BMI, testosterone, estradiol, prolactin, lipids, electrolytes, liver function tests, hemoglobin/hematocrit, and hemoglobin A1c were reviewed. These values were obtained from before the start of therapy, at 1 to 3 months after initiation, at 4 to 6 months, and at 6 months and beyond. Repeated measures analysis of variance models were used to evaluate changes over time. One hunderd and sixteen adolescents were included (72 female-to-male subjects and 44 male-to-female subjects). Of the 72 subjects taking testosterone, a significant increase in hemoglobin/hematocrit levels and BMI, as well as a decrease in high-density lipoprotein level, was recorded at each visit. No significant changes in any other parameter tested were found. Of the 44 subjects taking estrogen, no statistically significant changes were noted in the measured metabolic parameters. Testosterone use was associated with increased hemoglobin and hematocrit, increased BMI, and lowered high-density lipoprotein levels; estrogen was associated with lower testosterone and alanine aminotransferase levels. Otherwise, cross-sex hormone administration in adolescents was not associated with significant differences in the selected metabolic parameters over time.